Connecting Beyond the Classroom: Hybrid Communication Strategies and their Influence on Parent Participation in Rural Education - Amaquiton, Niña Mae A.; Cutillas, Anesito L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This case study investigates how hybrid communication strategies impact parental involvement at Pañas Elementary School in rural Cebu, Philippines. Using a qualitative single-case study design, the research explored how traditional methods (such as face-to-face meetings and printed notices) and digital tools (such as SMS and social media platforms) influence parent-school engagement. Data were gathered through semi-structured interviews and focus group discussions involving one school head, seven teachers, and ten parents. Thematic analysis revealed four core themes: Communication Channels, Customized Communication, Technology Integration, and Open and Transparent Communication. Findings highlight that parents appreciate communication that is timely, clear, and sensitive to local contexts. Mobile-based messaging and personal interactions were particularly valued for their convenience and reliability. These strategies resulted in two key outcomes: improved access to school information and stronger collaboration between parents and school personnel. The study emphasizes the need for inclusive, culturally responsive communication practices that foster trust, partnership, and shared accountability in education.